Reediciones y devociones. Historia textual de la prosa religiosa de sor Juana Inés de la Cruz - Gutiérrez Reyna, Jorge (El Colegio de México, 2023)
The purpose of the present article is to contribute to the study of the textual transmission of the religious prose written by sor Juana Inés de la Cruz and published in loose sheets in America: Ejercicios de la Encarnación, Ofrecimientos del rosario, Carta atenagórica and Protesta de la fe. In most of the cases, the complete testimonia are put together for the first time. Each of the texts is collated so as to trace its history and to lay the foundations for a future critical edition.